2017
DOI: 10.1007/s00429-017-1500-5
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the left inferior frontal gyrus in human originality

Abstract: Human creative cognition is commonly described as a twofold cyclic process that involves an idea generation phase and an idea evaluation phase. Although the evaluation phase makes a crucial contribution to originality, its underlying mechanisms have not received sufficient research attention. Here, we suggest that the left inferior frontal gyrus (lIFG) plays a major role in the interplay between the evaluation and generation networks and that inhibiting this region's activity may have an effect on "releasing" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 70 publications
3
34
0
Order By: Relevance
“…It is possible that the higher node activity in the cognitive control areas is related to ongoing evaluation of ideas (Beaty et al, 2016) but that most of those ideas were initially appropriate alleviating the need to communicate corrective information to the motor areas. New research investigating the role of IFG in a traditional alternative found that left IFG is involved in the evaluation of creative ideas, generated by neural structures associated with the DMN (Kleinmintz et al, 2018). During musical improvisation, the real-time demands of the task most likely involve continuous generation with concurrent evaluation (Norgaard, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the higher node activity in the cognitive control areas is related to ongoing evaluation of ideas (Beaty et al, 2016) but that most of those ideas were initially appropriate alleviating the need to communicate corrective information to the motor areas. New research investigating the role of IFG in a traditional alternative found that left IFG is involved in the evaluation of creative ideas, generated by neural structures associated with the DMN (Kleinmintz et al, 2018). During musical improvisation, the real-time demands of the task most likely involve continuous generation with concurrent evaluation (Norgaard, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The first one considers that ventral and dorsal caudal PFC regions have opposite roles in the generative and evaluative steps of divergent thinking. The activity of the ventrolateral PFC may be deleterious to the generation step that requires less control processes [32,64 ], while other prefrontal regions are important for the more controlled evaluation step [67] or for the inhibition of constraints [20]. The second one is to consider a balance between left and right ventrolateral PFC rather than the role of each region separately [78].…”
Section: Lesion Methods Fmri Methods Vbm Methodsmentioning
confidence: 99%
“…This may be because standard control tasks, such as object characterisation, also rely on the semantic control system, and so activity related to divergent thinking is not strong enough to survive the contrast. However, several studies have found an inhibitory role of the IFG (Beaty et al, 2016; Ivancovsky, Kleinmintz, Lee, Kurman, & Shamay‐Tsoory, 2018) with Kleinmintz et al (2017) suggesting evaluating original ideas was related to an increase in activation in the left IFG, whereas generating original ideas was related to inhibition of the left IFG.The IFG has also been said to control activation in the middle temporal gyrus (MTG) said to be important in both the semantic and default mode network (DMN), with Vartanian et al (2018) suggesting the IFG selects ideas that are generated by the MTG to produce responses consistent with the task demands.…”
Section: Introductionmentioning
confidence: 95%